2019
DOI: 10.1088/2043-6254/ab2e6f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesize and survey the drug loading efficiency of the porous nano silica modified by gelatin

Abstract: Recent research in drug delivery, gelatin stand out from all other natural polymer by its property such as biocompatible, biodegradable, reduced immunogenicity. Modify porous nano silica (PNS) by gelatin to use for drug delivery can avoid the detection of the human immune system. In this study, the coated PNS was successfully formed with spherical shape and diameter around 70 nm determined by transmission electron microscopy (TEM). Drug loading and release behaviors of doxorubicine@PNS-gelatin, in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Its action is based on three unrelated principles: extended drug circulation time, avoidance of RES (reticuloendothelial system) through the use of PEGylated nanoliposomes, and high and simple doxorubicin loading driven by a transmembrane ammonium sulfate gradient, which promotes drug release in the tumor. Other investigated DOX carriers include copper sulfide NPs [ 8 ], magnetite [ 9 ], and porous nanosilica [ 10 ]. However, AuNPs provide alternative approaches due to their very attractive application properties.…”
Section: Introductionmentioning
confidence: 99%
“…Its action is based on three unrelated principles: extended drug circulation time, avoidance of RES (reticuloendothelial system) through the use of PEGylated nanoliposomes, and high and simple doxorubicin loading driven by a transmembrane ammonium sulfate gradient, which promotes drug release in the tumor. Other investigated DOX carriers include copper sulfide NPs [ 8 ], magnetite [ 9 ], and porous nanosilica [ 10 ]. However, AuNPs provide alternative approaches due to their very attractive application properties.…”
Section: Introductionmentioning
confidence: 99%
“…In several works [ 74 , 140 , 141 , 142 ], the antitumour drug doxorubicin was encapsulated in the pores of mesoporous silica coated with gelatin (Gel) to investigate this drug’s pH-dependent controlled release behaviour and cytotoxicity. The results showed that this pH-sensitive MSN@Gel system was highly biocompatible and had remarkable drug loading behaviour.…”
Section: Stimuli That Control Drug Releasementioning
confidence: 99%
“…The results showed a DLE of 55.90% and a sustained release profile at physiological pH 7.4. Therefore, they concluded that DOX/PNS-gelatin NPs were a promising delivery platform for pH-responsive release of DOX [18].…”
Section: Gelatinmentioning
confidence: 99%